Small/medium market models of newspaper and broadcasting convergence in the midwest - Geissler, Kyle (My University, 2006)
There is a large body of research on a recent movement in the news media referred to as convergence. This practice of sharing resources between media organizations takes many forms and is found in major markets. Research has, so far, given little attention to convergence models being put in place in smaller markets. This qualitative analysis uses interviews to examine various models for implementing and operating convergence between newspaper and broadcast newsrooms at three organizations in the Midwest. Interviews and site visits with managers at converged sites uncovered training challenges and the problems of overcoming cultural differences between newsrooms. An analysis using diffusion theory helps show how smaller markets prove to be a fertile testing ground for newsroom convergence because of their size, versatility, and need to economize resources. This study recommends increased small market convergence efforts and ways large markets can emulate small market management conditions by centralizing management of a converged newsroom in order to create a flexible and successful convergence model.
This file was last viewed in Adobe Reader 7.0
Keywords: Press -- Middle West; Broadcast journalism -- Middle West; Convergence (Telecommunication); Mass media -- Ownership -- Middle West; News agencies -- Middle West